Increasing agricultural resilience and flood-proofing livelihoods in Bangladesh - Amarnath, Giriraj (2015)
Index-based flood insurance (IBFI) is an innovative approach to developing effective payout schemes for low-income, flood-prone communities. This project aims to integrate hi-tech modelling and satellite imagery with other data to predetermine flood thresholds, which could trigger speedy compensation payouts. Effective end-to-end solutions will be developed in collaboration with a range of organizations and experts from central and state government bodies, private insurance firms, community-based organizations (CBOs) and nongovernmental organizations (NGOs). The project will be piloted in selected locations of India and Bangladesh, making it the first attempt to develop IBFI at a large scale.